2011
DOI: 10.1002/hep.24324
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1–mediated autophagy protects against hepatocyte cell death and hepatic injury from infection/sepsis in mice

Abstract: Adaptive responses to sepsis are necessary to prevent organ failure and death. Cellular signaling responses that limit cell death and structural damage allow a cell to withstand insult from sepsis to prevent irreversible organ dysfunction. One such protective pathway to reduce hepatocellular injury is the up-regulation of heme oxygenase-1 (HO-1) signaling. HO-1 is up-regulated in the liver in response to multiple stressors, including sepsis and lipopolysaccharide (LPS), and has been shown to limit cell death. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(178 citation statements)
references
References 24 publications
9
166
2
1
Order By: Relevance
“…The expression of mitochondrial cytochrome c and Bcl-2 protein expression were decreased in the ZIR group. Based on these findings (11), as well as those of previous studies, we hypothesized that the decrease in HO-1 expression induced by ZnPP may reduce autophagy, thus increasing liver cell injury, and that this may partly occur through the activation of the mitochondrial apoptotic pathway.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The expression of mitochondrial cytochrome c and Bcl-2 protein expression were decreased in the ZIR group. Based on these findings (11), as well as those of previous studies, we hypothesized that the decrease in HO-1 expression induced by ZnPP may reduce autophagy, thus increasing liver cell injury, and that this may partly occur through the activation of the mitochondrial apoptotic pathway.…”
Section: Discussionsupporting
confidence: 60%
“…It has been demonstrated that the induction of heme oxygenase-1 (HO-1) attenuates liver cell injury, and that preconditioning with protoporphyrin Ⅸ zinc accentuates liver damage (10). A previous study reported that HO-1 attenuates liver injury by inducing autophagy and inhibiting cell apoptosis, and that a decrease in HO-1 activity increases cell apoptosis and thus accentuates liver injury (11). Therefore, it may be of interest to investigate the role of ZnPP in liver ischemia/reperfusion (IR) injury.…”
Section: Introductionmentioning
confidence: 99%
“…51 Conversely, administration of chloroquine abolishes autophagic flux, which results in the elevation of serum transaminase levels. 14 Compelling evidence confirms that autophagy in the liver is induced during the initial 4 h after CLP but declines after this point until 24 h. 11,14,19,36,51 The blockade of autophagic flux is demonstrated by reduced LAMP1 expression, accumulation of SQSTM1 and lack of colocalization of autophagosomes with lysosomes.…”
Section: Livermentioning
confidence: 87%
“…16,17 In support of this notion, newly tested therapeutic agents in animal models have targeted modulation of the same molecular pathway-autophagy. 10,[18][19][20][21][22] In this review, we discuss the role of autophagy in sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many reports have suggested that HO-1 signalling pathways have an important role in the regulation of autophagy (10) hepatocyte cell death and hepatic injury from infection/sepsis in mice (12). Moreover, in myocardial dysfunction, HO-1 can prevent cardiac dysfunction in streptozotocin-diabetic mice by reducing inflammation, oxidative stress, apoptosis and enhancing autophagy (13).…”
Section: Background and Evidencementioning
confidence: 99%